Assess the Effects of Back Massage to Improve Sleeping Pattern of the Postoperative Cardiothoracic Patients among the Selected Hospitals - Vaishali Tembhare; Menaka S.P. (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background : During the recovery time after cardiac surgery, some patients find that they have disturbed sleep.This is due to a combination of the effects of anesthesia, pain or discomfort in the area of the incisions, back,shoulder, and neck pain from manipulation of body during surgical procedure and the post-operative changesto daily routine and stress. Lack of sleep may cause fatigue; delay in recovery process and lead to prolongedhospitalization Therapeutic back massage has gained support as an intervention that improves the overallrelaxation of the body. Patients experience back massage as a calming, stimulating and effective measure ofsleep-inducing influence. Objectives: To assess the sleeping pattern of post operative cardiothoracic patientsbefore giving back massage, To assess the sleeping pattern of post operative cardiothoracic patients aftergiving back massage, To compare the difference between before and after massage effect on sleeping patternof post operative cardiothoracic patients, To correlate the effects of back massage with selected demographicvariables and to find out association between before and after back massage effects on sleeping pattern ofpost operative cardiothoracic patients. Material and Methods: An experimental method research with aconfiguration which is quasi experimental (non-randomized control group). This research was carried outin selected hospitals of the Vidharbha Region on postoperative cardiothoracic patient. Result: Statisticallysignificant difference was found in sleeping pattern score of postoperative cardiothoracic patients, beforeand after massage effect in experimental group. Conclusion: Massage evokes an aura of acceptance, bodyrespect and treatment. The intimate personal contact suggested in massage improves the bond between thenurse and the patient and this in effect provides an environment for wellbeing and healing. The present studyconcludes that back massage has an effect on improving the sleep pattern of postoperative cardiothoracicpatients in order to cope with the problem of postoperative sleep disruption that helps to recover early aftersurgery.